Absence of gut microbiota restoration following meropenem treatment in a systemic infection model - Filipe Moura Ribeiro; Camila Fontoura Acosta Ribeiro; Elizabete de Souza Cândido; Danieli Fernanda Buccini; Marlon Henrique Cardoso; Gislaine Greice de Oliveira Silva Silveira; Carolina Moura de Souza; Osmar Nascimento Silva; Gisele Braziliano de Andrade; Alanderson Rodrigues da Silva; Franciele Bathel da Mota; Sarah Saory Makimoto; et al. (npj Antimicrobials and Resistance)
Abstract Antibiotics have been shown to have unintended effects on the host by disrupting the beneficial microbiota. In this study, we explored and longitudinally monitored microbiota during and after antibiotic treatment for infection. We induced a systemic Escherichia coli infection in 45 BALB/c mice, with 25 as uninfected controls. The disease was treated with meropenem. The animals were evaluated longitudinally three times, including 3 hours, five days of treatment, and 30 days post-treatment. Intestinal, lung, blood, and peritoneal lavage samples were collected for analysis. Our findings show that meropenem effectively treated the lethal systemic infection caused by E. coli. Hematological parameters, crypt depth, and goblet cell numbers remained unchanged for 30 days post-antibiotic treatment. However, antibiotic treatment impaired the recovery of the gut microbiota, even 30 days post-treatment. This long-term meropenem impact on microbiota was observed in both infected and non-infected (saline-treated) groups. Alpha and beta diversity analyses did not indicate a microbiota recovery. Notably, Lactobacillus and Bacteroides decreased, while Clostridioides, Enterococcus, and Escherichia-Shigella increased. This study provides novel evidence that, even 30 days after meropenem treatment in a simulated E. coli infection, the intestinal microbiota does not recover, highlighting prolonged antibiotic-induced dysbiosis.